2015
DOI: 10.1063/1.4935061
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectron spectroscopic and computational study of (M–CO2)− anions, M = Cu, Ag, Au

Abstract: In a combined photoelectron spectroscopic and computational study of (M-CO2)(-), M = Au, Ag, Cu, anionic complexes, we show that (Au-CO2)(-) forms both the chemisorbed and physisorbed isomers, AuCO2(-) and Au(-)(CO2), respectively; that (Ag-CO2)(-) forms only the physisorbed isomer, Ag(-)(CO2); and that (Cu-CO2)(-) forms only the chemisorbed isomer, CuCO2(-). The two chemisorbed complexes, AuCO2(-) and CuCO2(-), are covalently bound, formate-like anions, in which their CO2 moieties are significantly reduced. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(9 citation statements)
references
References 53 publications
(41 reference statements)
1
8
0
Order By: Relevance
“…The NPA method has been found to be satisfactory in calculating the charge distribution within a cluster. [27][28][29][30][31][32][33]…”
Section: Experimental and Theoretical Methodsmentioning
confidence: 99%
“…The NPA method has been found to be satisfactory in calculating the charge distribution within a cluster. [27][28][29][30][31][32][33]…”
Section: Experimental and Theoretical Methodsmentioning
confidence: 99%
“…The fact that CO 2 is only physisorbed on Cu 6 perhaps illustrates the fact that this cluster, which has six Cu 3s electrons, has a particularly stable “magic number” electron count (6e) corresponding to a closed shell for the solution of the Schrödinger equation for an electron constrained to a circular disk. In water, chemisorption (on Cu 3 , Cu 4 , and Cu 5 ) involves CO 2 bending and cluster-to-CO 2 charge transfer, which is considerably higher in magnitude (− q CO 2 > 0.8) than in the gas phase, closer to the formatelike structure observed on Cu – in the gas phase . As in the gas phase, the linear physisorbed CO 2 molecule on Cu 6 has a small positive charge ( q CO 2 = +0.01).…”
Section: Resultsmentioning
confidence: 86%
“…It should be noted that, in a combined photoelectron spectroscopy and computational study, Bowen et al have reported the formation of a gas-phase complex between CO 2 and a single Cu − anion, which results in electron transfer and the formation of Cu(CO 2 − ), where the CO 2 − moiety is bent and bonded to Cu via the carbon atom, with the negative charge delocalized over the π* framework of the coordinated CO 2 , corresponding to a formate-like complex. 94 Interestingly, Cu − only forms the chemisorbed complex with CO 2 , whereas Ag − forms only a C-bound physisorbed complex (with quasi-Table 1. Adsorption Free Energies (ΔG ads /eV) and Geometries of the CO 2 * (CO 2 -Adsorbed Complexes) for Different Cu n (n = 3−6) Clusters in the Gas Phase and Water a a The net NBO charges on the adsorbed CO 2 molecule (q CO 2 ) are also listed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well established that metal atoms and anions may add CO 2 to form complexes in gas phase reactions, formally metal carbonites (MCO 2 ). Their preferred structures are shown in Scheme , which in the case of alkali and alkaline earth metals is the bidentate coordination of the metal to both oxygen atoms (κ 2 -O 2 C), while for transition metals, the metal typically binds to the carbon atom (η 1 -CO 2 ) or in a side-on fashion (η 2 -CO 2 ). Early transition metals, M = Sc, Ti, V, and Cr, ,, even insert into one of the C–O bonds with subsequent CO elimination: …”
Section: Introductionmentioning
confidence: 99%